Autowave plasticity : localization and collective modes - Zuev, Lev; Riecansky, V. E. (Boca Raton, FL : CRC Press, 2021)
Autowave Plasticity: Localization and Collective Modes discusses the nature of plastic flow in solids associated with the development of a localized plastic flow. Written by an authority in the field, the author demonstrates how patterns of localized plastic flow are associated with autowave modes that are generated in a deformable sample and delivers a complete work on the subject. Key Features An original work on the nature of plastic flows in solids, particularly metals and crystals Focuses on plastic flow as an autowave process Contains elements of theories, experimental considerations, and numerical modeling This reference will help readers with creating experimental methods to observe or localize plastic flow and with the modeling of plastic flows. It is a valuable reference for graduate students and research specialists working in material science.
OCLC-licensed vendor bibliographic record.
Keywords: Plasticity; Plastics -- Viscosity; TECHNOLOGY / Material Science; SCIENCE / Solid State Physics